SELF EFFICACY PEREMPUAN USIA 35 - 44 TAHUN DALAM UPAYA PENCEGAHAN KANKER PAYUDARA - Windi Susilowati; M. Bagus Qomaruddin (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
Based on data from Health Department of Surabaya on Reports Puskesmas in Surabaya at 2015 discovered that the number of breast cancer patients over the years also increased. More than 30% of cancer can be prevented with breast self examination (BSE). Puskesmas with BSE declining coverage in a row is a big health center coverage is Puskesmas Tembok Dukuh with 1.89% in 2014 and then declined in 2015 to 1.22%. This study used observational research and cross sectional design. Researchers took samples with simple random sampling with 33 respondents. Independent variables in this study is performance accomplishment, vicarious experience, social persuasion dan physiological and emotional states. And the dependent variables in this study is self effi cacy and BSE. Data analysis using cross tabulations. And the result that good performance accomplishment, vicarious experience, social persuasion dan physiological and emotional states it will have an impact on his self effi cacy. The conclusion of this study is the majority of respondents with good self effi cacy have a good BSE. Therefore it is necessary to increase the numbers of BSE coverage by increasing self effi cacy by providing values of motivation to be concerned about her reproductive health.